High-k Dielectric Thickness and Halo Implant on Threshold Voltage Control - Mah S.K.; Ahmad I.; Ker P.J.; Noor Faizah Z.A. (Universiti Teknikal Malaysia Melaka, 2023)
High-k dielectric oxides have been used to replace the widely used silicon dioxide (SiO2) gate dielectrics to overcome physical limits of transistor scaling. The thickness of high-k gate dielectric influences the threshold voltage (VTH) and off-state leakage current (IOFF). A device with high drive current (ION) and low IOFF gives a high on-off current ratio (ION/IOFF), which leads to a faster switching speed for the N-type Metal Oxide Semiconductor Field Effect Transistor (NMOS). In order to achieve the best ION/IOFF ratio for a predetermined range of VTH, halo implant was used to adjust the threshold voltage. The finding shows that optimum VTH and ION/IOFF ratio can be achieved by selecting the most suitable halo implant dose in a virtually fabricated 14nm gate-length La2O3-based NMOS device with varying high-k dielectric oxide thickness. 2018 Universiti Teknikal Malaysia Melaka. All rights reserved.